2015
DOI: 10.1002/fam.2338
|View full text |Cite
|
Sign up to set email alerts
|

The influence of melamine impregnation and heat treatment on the fire performance of Scots pine (Pinus sylvetris) wood

Abstract: Summary Wood, as a natural and renewable resource, is a popular material for construction, but its fire performance restricts its utilization. In addition, for example, the mechanical properties of wood have up till now been impaired by the most common fire retardants, and therefore, the investigation of wood modification with not‐weakening flame retardants is essential. This study investigates the effects of melamine impregnation and heat treatment on the fire performance of Scots pine (Pinus sylvetris L.). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The combined wood modification technology of resin impregnation and heat treatment (IMPG-HT) aims at not only improving mechanical properties and dimensional stability, but also enhancing the durability and changing the color of wood to imitate that high-performance precious wood. Thus, wood modified with this combined technology has great potential to be used in the field of high-grade furniture, flooring, special furniture and building [11][12][13][14][15]. Previous studies on IMPG-HT wood focused on treatment technology and properties improvement of wood after modification.…”
Section: Introductionmentioning
confidence: 99%
“…The combined wood modification technology of resin impregnation and heat treatment (IMPG-HT) aims at not only improving mechanical properties and dimensional stability, but also enhancing the durability and changing the color of wood to imitate that high-performance precious wood. Thus, wood modified with this combined technology has great potential to be used in the field of high-grade furniture, flooring, special furniture and building [11][12][13][14][15]. Previous studies on IMPG-HT wood focused on treatment technology and properties improvement of wood after modification.…”
Section: Introductionmentioning
confidence: 99%
“…reached similar conclusions [ 48 ]. Lahtela and Kärki impregnated thermally treated wood with melamine and found that the heat treatment reduced the HRR values, but melamine impregnation before heat treatment was able to raise it to a higher value [ 49 ]. The aforementioned values of the peak heat release rates are significantly higher than for torrefied wood, which may be ascribed to the significantly lower temperatures used for the thermal treatment (180–220 °C) as opposed those used in torrefaction.…”
Section: Resultsmentioning
confidence: 99%
“…Chinese historical buildings are In order to evaluate the possible impact of the above combustibles on Chinese historical buildings and the surroundings, it is necessary to learn the combustion and fire spread characteristics of different materials. Previous literatures have carried out some researches about wooden materials (Lahtela and Kärki 2016;Regan 2021;Liu et al 2013;Kuo and Hwang 2003), and recently, textiles and some soft materials are also paid attention because they are common and easy to be ignited as well (Yang and He 2012;An et al 2010;Kandola et al 2006;Wulff et al 1973). You et al (You, Hu, and Song 2007) compared 47 kinds of hanging decorative textiles in Tibet historical buildings for their pyrolysis and combustion characteristics, such as heat release rate (HRR), mass loss rate (MLR), peak gas volume fraction, etc.…”
Section: Introductionmentioning
confidence: 99%